Philosophizing Claude Wheeler’s Character in Willa Cather’s One of Ours (1922) - Bani-Khairc, Baker M.; Al-Anbar, Omar Abdullah; Al-Anbar, Khaled Abdullah (Technium Social Sciences Journal, 2023)
This paper attempts to explore the thematic dimensions of Claude Wheeler’s philosophy about life and death in Willa Cather’s One of Ours (1922) which seem to be vague and complex at the same time. This philosophy that Claude develops through his relationships with the surroundings and the persons around him governs the way he thinks and veers the torrent of thoughts that he made with himself in terms of several aspects pertaining to his psychological, romantic, spiritual, and military life. Despite the fact that Claude Wheeler is an ambiguous character who seeks for more harmony with his self, his personality weakness functions as a motivating factor for more self-development, and he deeply and philosophically recognizes that he can understand life much better through ideals and values.